Effect of Family Ownership, Leverage and Net Profit Margin on Profitability Case Study on Listed Company on BEI - Sri Rahayu; Ali Farhan; Wulandari Harjanti; Parwita Parwita (Budapest International Research and Critics University, 2022)
This research aims to analyze the effect of family ownership, leverage, and net income on company profitability. By using a sample of 33 companies listed on the Indonesia Stock Exchange and a quantitative approach with multiple linear regression analysis on SPSS v.16, the results show that only the net income variable has a significant effect on company profitability, while family ownership and leverage have no significant effect.